Preparation method of C-TaC / SiC high-temperature corrosion-resistant coating

By depositing C-TaC/SiC double-layer coating on the surface of carbon materials, the corrosion problem of traditional carbon materials in high temperature environments is solved, and higher corrosion resistance and stability are achieved.

CN119710629APending Publication Date: 2025-03-28INDAF ADVANCED MATERIALS (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927030.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional carbon materials cannot effectively deal with corrosion problems in high-temperature extreme environments, resulting in production quality and cost problems.

Method used

Using a C-TaC/SiC double-layer coating structure, the first layer of C-TaC composite coating and the second layer of SiC coating are deposited on the surface of carbon materials through low-temperature chemical vapor deposition technology to improve the bond strength and compatibility of the coating and the substrate.

Benefits of technology

It improves the high-temperature corrosion resistance of carbon materials, reduces the difference in thermal expansion coefficient, and enhances the overall stability and protection performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710629A_ABST
    Figure CN119710629A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a C-TaC / SiC high-temperature corrosion-resistant coating. The method comprises the following steps: pretreating the surface of a carbon material to achieve cleaning and hole sealing effects; then placing in a low-temperature chemical vapor deposition furnace to deposit a first C-TaC complex phase coating, after high-flow propylene is heated and decomposed, depositing one part on the surface of the carbon material to generate a pyrolytic carbon coating, and reacting the other part with low-flow tantalum pentachloride gas to generate tantalum carbide which is dispersively distributed in the pyrolytic carbon coating; after the preparation of the first C-TaC coating is finished, continuously preparing a second SiC coating, introducing trichloromethylsilane into the reaction chamber through hydrogen, and generating a SiC coating on the surface of the C-TaC coating under the reduction action of the hydrogen; in the C-TaC / SiC double-layer coating structure, the high-component pyrolytic carbon can effectively improve the bonding strength of the coating and a matrix, reduce the difference of thermal expansion coefficients and facilitate the improvement of the compatibility with the second SiC coating; and a trace amount of tantalum carbide can be pinned on the surface of a matrix as a hard phase, so that the overall stability of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical vapor deposition, and in particular to a method for preparing a C-TaC / SiC high-temperature corrosion-resistant coating. Background Art

[0002] With the development and progress of science and technology, the rapid rise of industries such as communication technology, new energy vehicles, and smart grids has given the semiconductor industry and its related fields broad application prospects. In the semiconductor manufacturing process, high-temperature corrosion environments are common in links such as substrates and epitaxial wafers. However, traditional carbon materials cannot effectively cope with the challenges under the above extreme conditions, leading to a series of production quality and cost issues, such as products being scrapped due to pollution, equipment damage, and reduced service life. Therefore, it is extremely important to improve the corrosion resistance of related carbon materials. It is an ideal measure to coat the surface of carbon materials with corrosion-resistant coatings. For the corrosion protection of carbon materials in high temperature environments, the current focus at home and abroad is on coating the working surface of carbon materials with pyrolytic carbon coatings, or silicon-based coatings represented by SiC, or transition metal carbide (TaC, ZrC, etc.) coatings as high-temperature protection for carbon materials, and the coatings prepared by chemical vapor deposition technology (CVD) have the best performance. The advantage of chemical vapor deposition technology is that it has a wide range of product precursor selection, can design and control the composition and structure of the coating, and can prepare high-melting point materials at lower temperatures. The equipment is relatively simple and easy to operate, and through the transformation and optimization of the equipment, a gradient coating or a composite coating can be deposited in one go by co-deposition. At present, the technology of preparing a single coating on the surface of carbon materials by CVD is relatively mature, but due to the mismatch in thermal expansion coefficients between the single coating and the carbon material substrate, microcracks and pores are easily formed between the coating and the substrate under extreme high temperature conditions, affecting the overall protective performance of the coating. Therefore, a multilayer coating system or a composite coating system is developed to utilize the characteristics of different elements in the coating to prepare a coating with advantages such as low stress and good adhesion, so as to achieve the best corrosion protection for carbon materials. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a C-TaC / SiC high-temperature corrosion-resistant coating, wherein the surface of the carbon material is pretreated to improve the surface state of the material to be deposited, thereby achieving the effects of cleaning and sealing; then, the first layer of C-TaC multiphase coating is deposited in a low-temperature chemical vapor deposition furnace, and a portion of high-flow propylene is thermally decomposed and deposited on the surface of the carbon material to form a pyrolytic carbon coating, and the other portion reacts with a low-flow tantalum pentachloride gas to form tantalum carbide, which is dispersed in the pyrolytic carbon coating; after the preparation of the first layer of C-TaC coating is completed, the second layer of SiC coating is continuously prepared, trichloromethylsilane is brought into the reaction chamber by hydrogen, and a SiC coating is formed on the surface of the C-TaC coating under the reduction effect of hydrogen; in the above-mentioned C-TaC / SiC double-layer coating structure, the high-component pyrolytic carbon can effectively improve the bonding strength between the coating and the substrate, reduce the difference in thermal expansion coefficient, and is conducive to improving the compatibility with the second layer of SiC coating; a trace amount of tantalum carbide can be pinned on the surface of the substrate as a hard phase to improve the overall stability of the coating.

[0004] Technical solution: A method for preparing a C-TaC / SiC high temperature corrosion resistant coating, comprising the following steps: Step 1: Surface treatment of carbon material: The surface of the carbon material is polished with silicon carbide sandpaper of 2000 mesh or more, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 80 to 120° C. for 1 to 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: the treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the diluent gas and carrier gas; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 200-300° C. through an automatic temperature control heating device to evaporate it, and then argon is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 900-1200° C., the deposition time is 1-30h, and the deposition pressure is 0.1-80KPa, and a C-TaC coating with a thickness of 5-50μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 900-1200°C, the deposition time is 1-30h, and the deposition pressure is 0.1-100KPa, and a SiC coating with a thickness of 10-100μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 1 to 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Furthermore, the carbon material in step (1) includes graphite material, carbon / carbon composite material and carbon fiber hard felt material. Furthermore, before the surface treatment of the carbon fiber hard felt material, a layer of slurry needs to be coated on the surface of the carbon fiber hard felt material, and then placed in a drying oven and dried at a temperature of 80 to 120° C. for 1 to 2 hours. Furthermore, the coating method is spraying, brushing or dipping. Furthermore, the slurry is graphite powder or carbon powder added with adhesive PVB, dissolved in ethanol and mixed into a paste. Furthermore, the mass ratio of the carbonaceous powder, the adhesive PVB and the ethanol is (70-90):(1-10):(10-30). Furthermore, the modification method of the modified low-pressure chemical vapor deposition furnace in step (2) is as follows: modify the traditional low-temperature chemical vapor deposition furnace, use the gas pipeline to connect the tantalum pentachloride evaporator and the trichloromethylsilane supporting steel tank to the furnace body at the same time; fix the heating device on the air inlet pipeline of the tantalum pentachloride evaporator; place a water bath heater under the trichloromethylsilane steel tank; prepare the C-TaC coating by controlling the gas flow meter valves of propylene and argon respectively; and prepare the SiC coating by adjusting the gas valve of hydrogen. Furthermore, in the step (2), the molar ratio of tantalum pentachloride gas to propylene gas is (0.1-0.4):1; the molar ratio of propylene to diluent gas argon gas is 1:(1-15). Furthermore, in step (3), the molar ratio of trichloromethylsilane, hydrogen and argon gases is (0.1-1):(1-10):(0.5-6). Beneficial effects: 1. The present invention transforms the traditional low-temperature chemical vapor deposition equipment so that one device can simultaneously deposit single, multi-layer, complex and gradient coatings. 2. The present invention first pre-treats the surface of the carbon material (graphite, carbon-carbon composite material and carbon fiber hard felt) to improve the surface state of the material to be deposited, so as to achieve the effect of cleaning and sealing; then, the first layer of C-TaC composite coating is deposited in a low-temperature chemical vapor deposition furnace, and a part of the high-flow propylene is thermally decomposed and deposited on the surface of the carbon material to form a pyrolytic carbon coating, and the other part reacts with a low-flow tantalum pentachloride gas to form tantalum carbide, which is dispersed in the pyrolytic carbon coating; the molar fraction ratio of pyrolytic carbon to tantalum carbide is (1-10) %: (90-9 9)%; after the preparation of the first layer of C-TaC coating is completed, the second layer of SiC coating is continued to be prepared, trichloromethylsilane is brought into the reaction chamber by hydrogen, and a SiC coating is generated on the surface of the C-TaC coating under the reduction effect of hydrogen; in the above-mentioned C-TaC / SiC double-layer coating structure, the high-component pyrolytic carbon can effectively improve the bonding strength between the coating and the substrate, reduce the difference in thermal expansion coefficient, and is conducive to improving the compatibility with the second layer of SiC coating; a trace amount of tantalum carbide can be pinned on the surface of the substrate as a hard phase to improve the overall stability of the coating. 3. The process of the present invention is simple and easy to operate. During chemical vapor deposition, coatings of different proportions, components and structures can be deposited on the surface of the carbon material by only heating once. The coating is well bonded to the substrate, has no pores or interlayer cracks, and has excellent corrosion resistance. It is suitable for high-temperature corrosion protection of materials such as graphite, carbon / carbon composite materials, and carbon fiber hard felt. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a surface scanning electron microscope photograph of the C-TaC / SiC high temperature corrosion resistant coating deposited on the surface of the carbon material in Example 1; Figure 2 This is a cross-sectional scanning electron microscope photograph of the C-TaC / SiC high temperature corrosion resistant coating deposited on the surface of the carbon material in Example 1. DETAILED DESCRIPTION Example 1 A method for preparing a C-TaC / SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon / carbon composite materials: The surface of the carbon / carbon composite materials is polished with silicon carbide sandpaper of 2000 mesh or above, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 100°C for 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: The treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the dilution gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.1:1; propylene and The molar ratio of the diluent gas and the argon gas is 1:2; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C through an automatic temperature control heating device to evaporate it, and then the argon gas is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 950°C, the deposition time is 10h, and the deposition pressure is 0.4KPa, and a C-TaC coating with a thickness of 10μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the molar ratio of trichloromethylsilane, hydrogen and argon is 0.2:1:0.8; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1050°C, the deposition time is 8h, and the deposition pressure is 0.6KPa, and a SiC coating with a thickness of 20μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Example 2 A method for preparing a C-TaC / SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon / carbon composite materials: The surface of the carbon / carbon composite materials is polished with silicon carbide sandpaper of 2000 mesh or above, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 100°C for 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: The treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the dilution gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.2:1; propylene and The molar ratio of the diluent gas argon gas is 1:3; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C through an automatic temperature control heating device to evaporate it, and then the argon gas is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 1000°C, the deposition time is 15h, and the deposition pressure is 0.6KPa, and a C-TaC coating with a thickness of 15μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the molar ratio of trichloromethylsilane, hydrogen and argon is 0.5:2:3; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1100°C, the deposition time is 12h, and the deposition pressure is 0.8KPa, and a SiC coating with a thickness of 30μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Example 3 A method for preparing a C-TaC / SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon / carbon composite materials: The surface of the carbon / carbon composite materials is polished with silicon carbide sandpaper of 2000 mesh or above, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 100°C for 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: The treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the dilution gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.4:1; propylene and The molar ratio of the diluent gas argon gas is 1:6; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C through an automatic temperature control heating device to evaporate it, and then the argon gas is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 1100°C, the deposition time is 20h, and the deposition pressure is 1.0KPa, and a C-TaC coating with a thickness of 20μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the molar ratio of trichloromethylsilane, hydrogen and argon is 1:5:3; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1150°C, the deposition time is 16h, and the deposition pressure is 1.2KPa, and a SiC coating with a thickness of 45μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Example 4 A method for preparing a C-TaC / SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon fiber hard felt material: spray a layer of slurry on the surface of the carbon fiber hard felt material, the slurry is graphite powder added with adhesive PVB, dissolved and mixed into a paste by ethanol, the mass ratio of graphite powder, adhesive PVB and ethanol is 70:5:25, placed in a drying oven at a temperature of 100°C for 2h; the surface is then polished with silicon carbide sandpaper above 2000 mesh, ultrasonically cleaned for 30min, placed in a drying oven at a temperature of 100°C for 2h to obtain the treated carbon material; Step 2: C-TaC coating deposition: the treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the diluent gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.2:1; the molar ratio of propylene to the diluent gas argon gas is 1:2; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C through an automatic temperature control heating device to evaporate it, and then argon is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 1000°C, the deposition time is 15h, and the deposition pressure is 1.0KPa, and a C-TaC coating with a thickness of 15μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the molar ratio of trichloromethylsilane, hydrogen and argon is 0.3:1:1.5; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1100°C, the deposition time is 15h, and the deposition pressure is 1.2KPa, and a SiC coating with a thickness of 35μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Example 5 A method for preparing a C-TaC / SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon fiber hard felt material: spray a layer of slurry on the surface of the carbon fiber hard felt material, the slurry is graphite powder added with adhesive PVB, dissolved and mixed into a paste by ethanol, the mass ratio of graphite powder, adhesive PVB and ethanol is 85:5:10, placed in a drying oven at a temperature of 100°C for 2h; the surface is then polished with silicon carbide sandpaper above 2000 mesh, ultrasonically cleaned for 30min, placed in a drying oven at a temperature of 100°C for 2h to obtain the treated carbon material; Step 2: C-TaC coating deposition: the treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the diluent gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.3:1; the molar ratio of propylene to the diluent gas argon gas is 1:3; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C through an automatic temperature control heating device to evaporate it, and then argon is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 1100°C, the deposition time is 20h, and the deposition pressure is 1.0KPa, and a C-TaC coating with a thickness of 20μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the molar ratio of trichloromethylsilane, hydrogen and argon is 0.5:5:3; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1150°C, the deposition time is 20h, and the deposition pressure is 1.2KPa, and a SiC coating with a thickness of 40μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Comparative Example 1 The difference between this embodiment and embodiment 2 is that a single layer of C-TaC coating is deposited, as follows: A method for preparing a C-TaC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon / carbon composite materials: The surface of the carbon / carbon composite materials is polished with silicon carbide sandpaper of 2000 mesh or above, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 100°C for 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: The treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the dilution gas and carrier gas; the molar ratio of tantalum pentachloride gas to propylene gas is 0.2:1; the molar ratio of propylene to dilution gas is 0.2:1; the molar ratio of propylene to dilution gas is 0.2:1. The molar ratio of the released gas to the argon gas is 1:(5); the solid tantalum pentachloride powder is loaded into the evaporator and heated to 250°C by an automatic temperature control heating device to evaporate it, and then the argon gas is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 1050°C, the deposition time is 20h, and the deposition pressure is 0.8KPa, and a C-TaC coating with a thickness of 20μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Comparative Example 2 The difference between this embodiment and embodiment 2 is that a single-layer C-SiC coating is deposited, as follows: A method for preparing a C-SiC high temperature corrosion resistant coating comprises the following steps: Step 1: Surface treatment of carbon / carbon composite materials: The surface of the carbon / carbon composite material is polished with silicon carbide sandpaper of 2000 mesh or above, ultrasonically cleaned for 30 minutes, and placed in a drying oven at 100°C for 2 hours to obtain the treated carbon material; Step 2: Deposition of C-SiC coating: trichloromethylsilane is used as the silicon source and carbon source, and propylene is introduced to increase the carbon content of the coating; hydrogen is used as the reaction gas and carrier gas; argon is used as the diluent gas; the molar ratio of trichloromethylsilane, propylene, hydrogen and argon gas is 0.3:1:5:3; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 1000°C, the deposition time is 20 hours, and the deposition pressure is 1.5KPa to obtain a SiC coating with a thickness of 40μm; Step 3: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling. Combined with the actual operating conditions of the silicon carbide crystal growth furnace for semiconductors, the experimental temperature was set at 1600°C and the corrosion resistance of the above coating was tested. The specific method is: first, the silicon material is placed in a graphite crucible, and the carbon material with the prepared coating is placed on the graphite crucible. The graphite crucible is covered so that the silicon vapor contacts the carbon material on one side, and then the crucible is placed in a vacuum carbon tube furnace, and the temperature is increased to the set experimental temperature at a rate of 10°C / min for insulation. High-purity argon gas is used for protection throughout the experimental process. As the temperature rises, a large amount of silicon vapor will be generated after the silicon material melts, and a siliconization reaction will occur when it diffuses to the surface of the carbon material. After 10 hours of corrosion under the above conditions, the appearance of the coating is observed and the corrosion rate is calculated by weight loss. The results are shown in Table 1 below: Table 1 Appearance Corrosion rate Example 1 The coating remains intact without cracking or peeling 0.16μm / h Example 2 The coating remains intact without cracking or peeling 0.15μm / h Example 3 The coating remains intact without cracking or peeling 0.12μm / h Example 4 The coating remains intact without cracking or peeling 0.21μm / h Example 5 The coating remains intact without cracking or peeling 0.29μm / h Comparative Example 1 The coating remains intact without cracking or peeling 0.28μm / h Comparative Example 2 The coating remains intact without cracking or peeling 0.21μm / h

Claims

1. A method for preparing a C-TaC / SiC high temperature corrosion resistant coating, characterized in that: The following steps are involved: Step 1: Surface treatment of carbon material: The surface of the carbon material is polished with silicon carbide sandpaper of 2000 mesh or more, ultrasonically cleaned for 30 minutes, and dried in a drying oven at 80 to 120° C. for 1 to 2 hours to obtain the treated carbon material; Step 2: C-TaC coating deposition: the treated carbon material is placed in a modified low-pressure chemical vapor deposition furnace, with tantalum pentachloride as the tantalum source; propylene as the carbon source; argon as the diluent gas and carrier gas; the solid tantalum pentachloride powder is loaded into the evaporator and heated to 200-300° C. through an automatic temperature control heating device to evaporate it, and then argon is used as a carrier gas to carry it into the reactor; at the same time, the gas valve is opened to introduce propylene to participate in the reaction, and the final deposition temperature is 900-1200° C., the deposition time is 1-30h, and the deposition pressure is 0.1-80KPa, and a C-TaC coating with a thickness of 5-50μm is obtained; after the deposition of the C-TaC coating is completed, the pipeline valve of the tantalum pentachloride evaporator and the propylene inlet valve are closed; Step 3: SiC coating deposition: trichloromethylsilane is used as silicon source and carbon source; hydrogen is used as reaction gas and carrier gas; argon is used as diluent gas; the trichloromethylsilane in the reaction tank is heated in a 35°C water bath and then loaded into the reaction chamber of the chemical vapor deposition furnace with hydrogen; the final deposition temperature is 900-1200°C, the deposition time is 1-30h, and the deposition pressure is 0.1-100KPa, and a SiC coating with a thickness of 10-100μm is obtained; Step 4: Cooling and taking out of the furnace: After the above coating deposition is completed, argon gas is filled into the furnace to make the furnace pressure reach a slightly positive pressure state; when the temperature is reduced to 300°C at a rate of 1 to 10°C / h, the heating power is turned off, and the furnace is taken out of the furnace after natural cooling.

2. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 1, characterized in that: The carbon material in step (1) includes graphite material, carbon / carbon composite material and carbon fiber hard felt material.

3. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 2, characterized in that: Before the surface treatment of the carbon fiber hard felt material, a layer of slurry needs to be coated on the surface of the carbon fiber hard felt material, and then placed in a drying oven and dried at a temperature of 80 to 120° C. for 1 to 2 hours.

4. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 3, characterized in that: The coating method is spraying, brushing or dipping.

5. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 3, characterized in that: The slurry is prepared by adding graphite powder or carbon powder into adhesive PVB, which is dissolved in ethanol and mixed into a paste.

6. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 5, characterized in that: The mass ratio of the carbonaceous powder, the adhesive PVB and the ethanol is (70-90):(1-10):(10-30).

7. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 1, characterized in that: The modification method of the modified low-pressure chemical vapor deposition furnace in the step (2) is as follows: modifying a conventional low-temperature chemical vapor deposition furnace, connecting a tantalum pentachloride evaporator and a trichloromethylsilane supporting steel tank to a furnace body at the same time by using a gas pipeline; fixing a heating device on an air inlet pipeline of the tantalum pentachloride evaporator; placing a water bath heater under the trichloromethylsilane steel tank; preparing a C-TaC coating by controlling the respective gas flow meter valves of propylene and argon; and preparing a SiC coating by adjusting the gas valve of hydrogen.

8. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 1, characterized in that: In the step (2), the molar ratio of tantalum pentachloride gas to propylene gas is (0.1-0.4):1; the molar ratio of propylene to diluent gas argon gas is 1:(1-15).

9. The method for preparing a C-TaC / SiC high temperature corrosion resistant coating according to claim 1, characterized in that: The molar ratio of trichloromethylsilane, hydrogen and argon in step (3) is (0.1-1):(1-10):(0.5-6).